Skeletal muscle gauge as a prognostic factor in patients with colorectal cancer - In Kyu Park (Wiley, 2021)
Abstract Background Although skeletal muscle index (SMI) and radiodensity (SMD) are well‐known prognostic factors, the clinical impact of the integrated measure, known as skeletal muscle gauge (SMG), has been limited in patients with colorectal cancer (CRC). Patients and Methods A total of 727 and 268 patients with CRC at two tertiary centers were included and allocated into the training and test sets, respectively. Preoperative slice computed tomography images of the third lumbar area were evaluated for SMI and SMD. SMG was calculated as SMI × SMD and expressed as an arbitrary unit (AU). The optimal cutoff SMG value was determined to maximize the overall survival (OS) difference between the groups with respect to sex in the training set. The multivariate Cox proportional hazard model evaluated the association of its clinical significance. Results With regard to SMG, 1640 and 1523 AU were identified as cutoff values for males and females, respectively. The patients with low SMG values showed significantly worse 5‐year OS than those with high SMG values in the two datasets (both p < 0.001). In the multivariate analysis, low SMG was identified as an independent poor prognostic factor of OS in the training set (hazard ratio 2.18, 95% confidence interval 1.43–3.32, p < 0.001) and test set (hazard ratio 1.79, 95% confidence interval 1.07–3.00, p = 0.025), whereas SMI and SMD were not. Conclusion SMG acts synergistically to improve its prognostic predictive accuracy as compared with SMI or SMD alone in patients with CRC. Additional research is warranted to define its significance in different ethnic groups.